Mengembangkan HRM Berdasarkan Nilai: Mengintegrasikan Prinsip Etika Islam ke dalam Praktik Human Resource Managament Modern - Kholili, Isa; Irsyada, M Rihal (Moderasi : Journal of Islamic Studies, 2025)
This study explores the integration of Islamic ethical principles into modern Human Resource Management (HRM) practices to respond to the global shift toward value-based and human-centered management models.A systematic literature review was conducted using Scopus, Web of Science, and other major databases. Thematic analysis was applied to identify how Islamic ethics—such as amanah, adl, ta’awun, sabr, and shura—are operationalized within HRM functions. The findings indicate that these ethical values can be embedded into recruitment, training, performance appraisal, compensation, and leadership systems. Their integration enhances organizational justice, employee engagement, cooperation, resilience, and decision-making effectiveness.Islamic ethics provide a relevant moral framework for shaping holistic, ethical, and sustainable HRM models. The study offers a conceptual alternative to conventional HRM approaches that tend to be materialistic and individualistic, demonstrating the potential of Islamic values to address contemporary organizational challenges.